PENGARUH PENCAMPURAN BIOETHANOL SEBAGAI BAHAN BAKAR TERHADAP PERFORMA MESIN DAN EMISI GAS BUANG PADA MOTOR BENSIN EMPAT LANGKAH SATU SILINDER - Cahya Raiza Mahendra; I Wayan Sugita; Darwin Rio Budi Syaka (Universitas Negeri Jakarta, 2022)
Indonesia's limited fossil energy reserves trigger the emergence of the fuel crisis problem in Indonesia. To overcome the problems of fuel scarcity several ways can be done, among others, by mixing fuel and bioethanol. The use of bioethanol is one of the efforts to utilize biomass energy sources because bioethanol is an environmentally friendly alternative fuel. For this reason, the author mixed the fuel RON 88 and bioethanol with the percentage of fuel variations 100% RON 88 (E0),10% bioethanol-90% RON 88 (E10), 20% bioethanol-80% RON 88 (E20). The research method used in this study is an experimental method carried out in the laboratory using a four-stroke gasoline motor. Variations of engine speed used are 3000 rpm, 4000 rpm, 5000 rpm, 6000 rpm, and 700 rpm. Then search fuel mixture is tested alternately through a motorcycle connected to the chassis dynamometers and exhaust gas analyzer. Based on the test results, the use of bioethanol as a fuel mixture for RON 88 is proven to be able to increase power and torque and reduce exhaust emissions. The test results show that the best increase in power and torque when using a mixture of RON 88 fuels and 20% bioethanol (E20) with a percentage increase in torque of 0.1 Nm (2.12%) and a maximum power of 0.01 kW (0.53%), as well as fuel consumption. Fuel consumption decreases by 0.001 ml/second date engine speed of 3000 rpm to 5000 rpm. And the best reduction in exhaust emission testing for CO and HC levels was obtained when using a mixture of RON 88 fuel and 20% bioethanol (E20).